2022
DOI: 10.1177/18632521221080476
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Ponseti management in preterm infants with clubfoot at term age

Abstract: Purpose: Currently, the optimal time to initiate treatment among preterm infants with clubfoot is unknown. The aim of this study was to describe treatment outcomes up to 1 year post-correction following Ponseti management in infants who were born preterm but treated at term age. Methods: A retrospective chart audit was conducted at a major pediatric hospital on preterm infants with clubfoot who commenced Ponseti management at term age (≥37 weeks of gestation). Data are expressed as mean values (±standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Scanlan et al reported that Ponseti treatment for clubfoot may be delayed until term age in premature infants (<37-week gestation) without an increased risk of recurrence. Both idiopathic and syndromic clubfeet were included; on average, 5.9 casts were needed for idiopathic clubfeet and 6.1 were needed for syndromic clubfeet 55 .…”
Section: Footmentioning
confidence: 99%
“…Scanlan et al reported that Ponseti treatment for clubfoot may be delayed until term age in premature infants (<37-week gestation) without an increased risk of recurrence. Both idiopathic and syndromic clubfeet were included; on average, 5.9 casts were needed for idiopathic clubfeet and 6.1 were needed for syndromic clubfeet 55 .…”
Section: Footmentioning
confidence: 99%
“…Scalan et al retrospectively reviewed 26 preterm infants (46 feet) born at < 37 weeks of gestation with clubfoot who were treated at term. They found that at one year follow-up they had comparable outcome, number of casts, tenotomy, and recurrence rates to those born at term [ 35 ].…”
Section: Introductionmentioning
confidence: 99%